1986
DOI: 10.1111/j.1600-0765.1986.tb01447.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of octenidine mouthrinse on plaque formation and gingivitis in humans

Abstract: Octenidine, a new bispyridine mouthrinse, has been shown to prevent plaque formation in humans over a seven‐day period. The purpose of the present study was to determine the effects of octenidine on plaque and gingivitis development in humans using a 21‐day experimental gingivitis model. Eighty‐eight subjects with a Plaque Index (PII) and Gingival Index (GI) ≤ 0.4 were randomly assigned to 4 coded formulations: 1) 0.1% octenidine in mouthwash vehicle used 3 times a day (TID), 2) 0.1% octenidine in mouthwash ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…It should be noted, however, that despite the lack of a significant difference in vitro between Hexoral and Corsodyl masked by the large variation for Hexoral, there was still a log step difference in biofilm CFUs following treatment with the two products. Twicedaily mouthrinsing with a formulation containing 0.1% octenidine almost completely inhibited plaque formation in a 7-day plaque regrowth trial [Patters et al, 1983] and during 21 days in the absence of mechanical toothcleaning [Patters et al, 1986], and these observations were confirmed in a 3-month clinical trial [Beiswanger et al, 1990]. These data are consistent with the nearly complete eradication of viable counts by Octenisept Colourless observed in our biofilm model.…”
Section: Discussionsupporting
confidence: 79%
“…It should be noted, however, that despite the lack of a significant difference in vitro between Hexoral and Corsodyl masked by the large variation for Hexoral, there was still a log step difference in biofilm CFUs following treatment with the two products. Twicedaily mouthrinsing with a formulation containing 0.1% octenidine almost completely inhibited plaque formation in a 7-day plaque regrowth trial [Patters et al, 1983] and during 21 days in the absence of mechanical toothcleaning [Patters et al, 1986], and these observations were confirmed in a 3-month clinical trial [Beiswanger et al, 1990]. These data are consistent with the nearly complete eradication of viable counts by Octenisept Colourless observed in our biofilm model.…”
Section: Discussionsupporting
confidence: 79%
“…Octenidine hydrochloride (OCT), developed by Sterlig Winthrop Research Institute, is a bispyridine derivative, that is, N,N'‐[1,10‐decanediyldi‐1(4H)‐pyridinyl‐4‐ylidene] bis(1‐octanamine) dihydrochloride. The existing information suggests that a mouthrinse containing 0.1% OCT may be capable of exerting beneficial clinical effects upon plaque accumulation and gingivitis development (11–15). In oral rinse form, OCT was reported to inhibit dental plaque and caries in rats (16) and in humans (13).…”
Section: Introductionmentioning
confidence: 99%
“…Stability is given in the pH range 1·6–12·2, and under exposition to light and in contrast to chlorhexidine chloride OCT is not sensitive to hydrolysis and shows no reduction in the effect as a result of albumin or mucin (protein error) (1). It is levurocidal, effective against resident skin microflora and effects Gram positive and negative as well as plaque‐forming bacteria (1,3–8). Antibacterial effects of OCT on the oral microflora in vivo and in vitro are comparable to those of chlorhexidine gluconate and povidone‐iodine (9).…”
Section: Introductionmentioning
confidence: 99%